If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6y = 13fory Solving 5x + -6y = 13fory Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 5x + -6y + 6y = 13fory + 6y Combine like terms: -6y + 6y = 0 5x + 0 = 13fory + 6y 5x = 13fory + 6y Divide each side by '5'. x = 2.6fory + 1.2y Simplifying x = 2.6fory + 1.2y
| x(7x+9)=6 | | 3x^2-7xy-20y^2=0 | | 7(x-1)=6(x+4) | | 14x-9-3x-5=13x-3+3x | | 3(50)+12n=198 | | -7(w-8)-(5-6w)=-2w | | d^2-4d-3d=0 | | x+4/7=x-1/6 | | x^2-14xy-51y= | | 7.5=-0.5y | | 5w=-125 | | 13-9x=136-30 | | -90=-45f | | .75x=-8 | | 2x^2+7x+12=0 | | -5c=115 | | 3/4x=-8 | | -0.2d=9.8 | | x-4*10=7*5 | | P=x+2(3x-4) | | 1.5v=-30 | | 12k^2+2k-10=0 | | -10=5w | | y^2+6y+11=0 | | -6t=-120 | | 2x-y=1x+y | | 0.2g=-4 | | 2*3=18+x+5 | | 48b=-24 | | 5c=-405 | | -33x=11 | | x^2+24x-38=0 |